70th Year Anniversary of Carbon Nanotube Discovery-Focus on Real World Solutions - Paramsothy, Muralidharan (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue reprint highlights seventy years since the discovery of carbon nanotubes (CNTs) in 1952 by Russian scientists LV Radushkevich and VM Lukyanovich in what was then the Union of Soviet Socialist Republics or the USSR. It also reflects the popularization by the well-known Japanese scientist S Iijima, since 1991, of carbon nanostructures, including CNTs, towards nanotechnology as a forever impactful and inspiring field. For researchers, academics, and teachers of all levels, from novice to expert to guru, the articles contained within this Special Issue are themed around sustainability from nanotechnology, pertaining to diameter measurement, rotor system molecular simulation, ultra-high tensile strength, energy, filtration via membrane distillation, environmental remediation using adsorption, ionic liquids as curing agents, biosensors and bioinspired sensors, and electrical/mechanical properties of polymer nanocomposites. The CNT is a legacy 1D nanomaterial, only after which was 2D graphene able to emerge. This is a global and mixed-country authorship Special Issue, with this reprint containing articles from Canada, Saudi Arabia, China, Russia, Spain, India, Japan, the United Arab Emirates (UAE), the USA, Germany, Turkiye, and Malaysia. The Guest Editor is from Singapore and began publishing critical work on the CNT-polymer interface towards the mechanical properties of the nanocomposite up to 20 years ago.